DATA MINING AS A TECHNIQUE TO ANALYZE THE LEARNING STYLES OF STUDENTS IN USING THE LEARNING MANAGEMENT SYSTEM - Eka Miranda (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2011)
Higher education is becoming a big business, with huge investments in IT technology supporting LearningManagement System (LMS). LMS is a software application which is used by student in learning process. Thepurpose of this paper is to analyze the use of LMS based on activities and results of student learning and seeksto address the interface between individual learning that use LMS data to support decision-making and coursedesign. A model of data warehouse is built to evaluate by means of a case study the usefulness validity ofanalyses performed. Data mining is considered the non-trivial extraction of implicit, previously unknown, andpotentially useful information from data. This paper analyzes students’ activities records using LMS thenbuilding a data warehouse, and data mining. The paper finds that after mining data, students can be classifiedinto different groups according to the activities using LMS. The data mining results shows that students can becategorized into four clusters; each cluster has its own characteristics. Integration of data warehouse, datamining and LMS produce a framework that uses transactional data to be transformed into knowledge that canbe used to maximize the teaching-learning process of lecturer and students.